MODEL KINERJA KARYAWAN BERBASIS PARTISIPASI KERJA, STRES KERJA, DAN KOMPENSASI: STUDI PADA PT TIDAR KERINCI AGUNG SOLOK SELATAN - Rahmatullah Pratama; Dike Rama Putra (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
This study aims to determine the extent of the influence of work participation, work stress, and compensation on the employee performance of PT. Tidar Kerinci Agung Solok Selatan. The study consists of three independent variables, namely work participation, work stress, and compensation, and one dependent variable, employee performance. The analytical methods employed were correlation analysis and multiple regression analysis. Data were collected through questionnaires completed by employees of PT. Tidar Kerinci Agung Solok Selatan. Furthermore, based on the simultaneous hypothesis test (F-test), the calculated F-value was 19.077, which is greater than the F-table value of 2.76 (19.077 > 2.76), with a significance level of 0.000 (< 0.050). Therefore, it can be concluded that work participation, work stress, and compensation simultaneously have a positive and significant effect on employee performance. In addition, the coefficient of determination (R²) was found to be 0.467, or 46.7%. This indicates that 46.7% of the variation in employee performance can be explained by work participation, work stress, and compensation, while the remaining 53.3% is influenced by other variables not examined in this study.